Identification of design factors that contribute to the success of business premises at public plaza in urban tourism areas - Harun, Nor Zalina; Zakariya, Khalilah; Mansor, Mazlina (INSPEN, 2016)
This research examines design factors that contribute to the contribute to the operations and success of the business premises selling souvenirs and local products for tourists at the Heritage Bazaar in Dataran Pahlawan, Melaka. These business premises were previously kiosks ans stalls that sold merchandise to visitors who visited Padang Pahlawan a historical field located in the middle of Melaka Historic city. Now, the field has been redeveloped into a modern urban plaza that is located on the upper ground together with a new shopping mall. The business premises that originally located at the ground level were then relocated into permanent shop lots at the lower ground level of the new urban plaza and shopping mall. The relocation of the premises from the ground level of the lower ground level reported to have affected the sales of goods and merchandise that were intended to attract visitors and tourists, Embarking from the research problem, this study aims to underline and analyse the physical and functional dimensions of the Heritage Bazaar, the plaza and the surrounding context that influence its function in attracting the visitors and tourists. Based on the methods of mapping, interviews and survey questionnaire, this study found that the successful business premises rely strongly on the relationship and connectivity with its surrounding context. In this case, since the Heritage Bazar is a type of tourism shopping outlet, its link with the immediate tourist attractions and visitor activities need to be reinforced, reconnected and enhanced. Although the newly developed shop lots of the businesses, in replace of the previous temporary stalls and kiosks, gave opportunities for the vendors to have more stable and permanent shops, however, there is a loss a visibility and connectivity with tourist activities. Based on the findings of the study, among the strategies that can be proposed for the Heritage Bazar is to re-establish its design encompasses of seven design criteria with its immediate context.